Exploring the impact of workload, organizational support, and work engagement on teachers’ psychological wellbeing: a structural equation modeling approach - Wang, Yonggang (Frontiers in Psychology, 2024)
This study investigates the interplay between workload, perceived organizational support, work engagement, and psychological well-being among 572 secondary school teachers in China. Utilizing structural equation modeling (SEM), the study assessed construct validity and relationships among latent variables. The findings indicated significant negative associations between workload and organizational support, workload and work engagement, and workload and psychological well-being. Positive correlations were observed between organizational support, work engagement, and psychological well-being. The SEM analysis confirmed robust alignment with anticipated models, indicating strong fit indices. Mediation analyses revealed work engagement as a significant mediator in the relationships between workload and psychological well-being and between organizational support and psychological well-being. The results emphasize the pivotal role of work engagement in influencing the impact of workload and organizational support on teachers' psychological well-being in Chinese secondary schools.